First reported detection of biofilm formation by Campylobacter fetus during investigation of a case of prosthetic valve endocarditis. Issue 8 (4th May 2019) - Lynch, Caoimhe; O'Connor, James A; O'Brien, Deirdre; Vaughan, Carl; Bolton, Declan; Coffey, Aidan; Lucey, Brigid
Abstract : Aims: Campylobacter fetus subsp fetus (CFF) can cause intestinal illness, particularly in immunocompromised humans, with the potential to cause severe systemic infections. CFF is a zoonotic pathogen with a broad host range among farm animals and humans, inducing abortion in sheep and cows. The current paper describes a strain of CFF isolated from a patient with prosthetic valve endocarditis in Mercy University Hospital, Cork, Ireland, during 2017. Only five cases of C. fetus as a cause of prosthetic valve endocarditis have been reported in the literature, with no reports of biofilm formation within the species. Methods: The aetiological strain was speciated and subspeciated by the VITEK 2 NH card and matrix-assisted laser desorption ionisation time-of-flight mass spectrometry. CFF biofilm formation was analysed using a crystal violet staining method. C. jejuni National Collection of Type Cultures (NCTC) 11168 was used as a positive control organism. Strains were incubated statically in Mueller-Hinton broth and Mueller-Hinton broth supplemented with 0.025% sodium deoxycholate for 3 and 7 days at 37°C, microaerobically. Results: The CFF strain formed stronger attached biofilms on polystyrene plates on day 3 (72 hours) than the C. jejuni NCTC 11168 control strain, but were weaker than the control strain on day 7 in Mueller-Hinton broth. Monoculture of this C. fetus isolate was found to exist in three defined forms of biofilms (attached, air–liquid interface and floccules). Conclusions: This clinically significant C. fetus isolate showed considerable biofilm-forming capability, which we suggest conferred a survivalist advantage, contributing to the genesis of infective prosthetic valve endocarditis.